Conflito entre o direito à privacidade e os direitos à informação e à liberdade de expressão: uma solução possível - Kallajian, Manuela Cibim (2018)
The solution to the conflict between the right to privacy and the rights to information and freedom of expression is often sought by doctrine and jurisprudence. The present study presents a way to solve the conflict between such rights from the legal hermeneutics. For this purpose, the right to privacy, the right to information and the right to freedom of expression were analyzed separately, under the perspective of personality rights and fundamental rights, both in national and in comparative law. Common hypotheses have been suggested where the right to privacy conflicts with the rights to information and freedom of expression in order to examine how doctrine and case law address the issue by upraising the main weighting criteria used. After finding that it is an apparent conflict of norms, the solution to the deadlock is presented through the technique of weighting indicating the main criteria for weighing, which should serve as parameters for the judicial decision, always aiming at the principle of dignity of human person